Evaluation of the Al-Quran Memorization Program Using the CIPP (Context, Input, Process, Product) Model at SDIT Ma'arif Padang Panjang - Marniati; Adripen; Muhammad Yusuf Salam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research was motivated by problems with the tahfidz program at SDIT Ma'arif Padang Panjang, namely (1) inadequate infrastructure, (2) insufficient tahfidz teachers. This research aims to find out: (1) Evaluation of the Context of the Tahfidz Al Qur'an Program using the CIPP Model at SDIT Ma'arif Padang Panjang. (2) Evaluation of the Tahfidz Al Qur'an Program Input using the CIPP Model at SDIT Ma'arif Padang Panjang. (3) Evaluation of the Tahfidz Al Qur'an Program Process using the CIPP Model at SDIT Ma'arif Padang Panjang. (4) Evaluation of the Tahfidz Al Qur'an Product Program using the CIPP Model at SDIT SDIT Ma'arif Padang Panjang.The method used in this research is evaluative qualitative research. The research location is SDIT Ma'arif Padang Panjang. The research period is from June to July 2024. The subjects of this research are the principal, deputy principal for student affairs, tahfidz coordinator and tahfidz teacher. The instruments in this research are interview guidelines and documentation guidelines. Data collection techniques are interviews and documentation studies. The data validity guarantee techniques used are source triangulation and technical triangulation. The data analysis techniques used are: (1) Data reduction; (2) Presentation of data (3) Drawing conclusions and verification.The results of this research show that: (1) Evaluation of the context of the tahfidz program at SDIT Ma'arif shows that the analysis of unfulfilled needs is that the competence of tahfidz teachers is not yet optimal and the facilities and infrastructure to support the tahfidz program are not adequate. (2) Evaluation of tahfidz program inputs at SDIT Ma'arif Padang Panjang that tahfidz teacher competencies, funding sources, and learning facilities need to be improved. (3) Evaluation of the tahfidz program process at SDIT Ma'arif Padang Panjang shows that the implementation process of learning Qur'anic tahfidz is going according to plan and that the obstacles in the implementation of learning Qur'anic tahfidz are the lack of class time and the lack of Qur'anic tahfidz teachers. in one class. (4) The product evaluation of the tahfidz program at SDIT Ma'arif Padang Panjang shows that the achievement of the memorization target of the students is in line with the target, and students who take the tahfidz compre test are declared to have passed their memorization.